Interactive methods of teaching mathematics in traditional learning and learning with information and communication technologies application - Losieva, N. M.; Panova, A. Yu. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The article deals with the essence of interactive learning, its purpose and organizational forms, examples of interactive methods both in the case of traditional learning and using information and communication technologies are suggested. It is shown that interactive teaching methods contribute to the enhanced presentation of the material, allow students to work in a mode of self-control, creating a positive atmosphere, allow instant analysis and correction of the learning process. Series of interactive exercises aimed at promoting training and educational potential of students in mathematics are offered in the paper.